Education of the clinical embryology laboratory professional: development of a novel program delivered in a laboratory medicine department - Heather Shapiro, M.D; Theodore J. Brown, Ph.D; Pat Chronis-Brown, M.Sc; G. Scot Hamilton, Ph.D; Danielle C. Bentley, Ph.D; Rita Kandel, M.D; Avrum I. Gotlieb, M.D.C.M (Elsevier, 2023)
Clinical embryologists are responsible for the handling, evaluation, and care of human gametes and preimplantation embryos within the context of an assisted reproductive technology laboratory. They are integral members of a team of professionals who provide care for fertility patients. Despite the increasing recognition of clinical embryologists as professionals, training requirements, continuing professional development, and appropriate credentialing have lagged in several countries. In many cases, individuals enter the profession with training limited to technical aspects provided by individual laboratory directors through an apprenticeship model. In this article, we present the rationale for rigorous formal training in clinical embryology, introduce CanEMB competencies for practicing professional clinical embryologists that are founded on CanMEDs role principles, and present a nascent Masters of Health Sciences degree program in Laboratory Medicine with a specialization in clinical embryology. This 2-year program has unique features including a Clinical Embryology Skills Development Laboratory, research capstone project, and 200-hour placement within a practicing assisted reproductive technology laboratory. Importantly, this program is delivered through a university-based Department of Laboratory Medicine and Pathobiology in partnership with a Department of Obstetrics and Gynecology. Thus, this program represents a formal acceptance of clinical embryology as a clinical laboratory science. It can be adopted elsewhere to provide a relevant, robust education that will meet current and future needs of the profession.